A contribution to a Keynesian-Sraffian synthesis: Kregel on financial macroeconomics - Roncaglia, Alessandro (PSL Quarterly Review, 2025)
As a review of Kregel’s book Financial Macroeconomics (London: Anthem Press, 2024), the article illustrates Kregel’s original interpretation of Keynes and its compatibility with a Keynesian-Sraffian approach alternative to both mainstream economics and other heterodox theories. Kregel’s analysis focuses on the analytical relations between own rates of own return and own rates of monetary return for commodities and the rate of interest.